Respuesta :
Answer:
she wrote
[tex](-2)^3= 8\\instead\ of\ (-2)^3= -8[/tex]
Step-by-step explanation:
For proper understanding let us format the question properly
Given the expression
[tex]=(-2)^3(6-3)-5(2+3)\\=(-2)^3(3)-5(5)\\=8(3)-25\\= 24-25= -1[/tex]
Sandy's error can be observed in the second line of the solution where she made the mistake of writing [tex](-2)^3= 8[/tex] instead of [tex](-2)^3= -8[/tex]
hence the solution is supposed to be
[tex]=(-2)^3(6-3)-5(2+3)\\=(-2)^3(3)-5(5)\\=-8(3)-25\\= -24-25= -49[/tex]